2014
DOI: 10.12816/0023470
|View full text |Cite
|
Sign up to set email alerts
|

Framing Arab Spring Conflict : A Visual Analysis of Coverage on Five Transnational Arab News Channels

Abstract: Guided by framing theory, a quantitative content analysis was conducted on news programming from five transnational satellite news channels that broadcast to/from the Arab world-Al Jazeera, Al Jazeera English, Al Arabiya, Alhurra, and BBC Arabic. The project examined if differences exist between the networks, and between two dimensions of a network taxonomy-western and liberal commercial-in how Arab Spring news selection and content was visually framed. A systematic comparative analysis was conducted on visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…In addition, their comparative analysis of American and French news organizations found that on the aforementioned situations, the US media strongly relied more on the political authorities than the French ones. As far as 'Arab Spring' is concerned, Bruce (2014) proved the findings of Benson & Hallin (2007), which suggest that in times of unrest the western media outlets tend to rely more on the political authorities. Furthermore, many reporters described the Egyptian 'Arab Spring' as a story of civil unrest.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, their comparative analysis of American and French news organizations found that on the aforementioned situations, the US media strongly relied more on the political authorities than the French ones. As far as 'Arab Spring' is concerned, Bruce (2014) proved the findings of Benson & Hallin (2007), which suggest that in times of unrest the western media outlets tend to rely more on the political authorities. Furthermore, many reporters described the Egyptian 'Arab Spring' as a story of civil unrest.…”
Section: Methodsmentioning
confidence: 83%
“…This finding depends on the results of the other researchers of the field (Benson & Hallin, 2007;Bruce, 2014). Meanwhile, the Chinese news outlet was the only one that contained an economic framed news story.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The current study -part of a larger research project (Bruce, 2012;2014;2016) -employed a content analysis, which examined visual images presented by five Arab media outlets -Al Jazeera, Al Jazeera English, Alhurra, BBC Arabic, and Al Arabiya. The five networks were chosen because they represent some of the most popular and controversial 24-hour news channels in the Arab world.…”
Section: Methods Network Taxonomymentioning
confidence: 99%
“…One of the most important developments has been the favourable treatment of Arabs by the media but a sea-change representation of Arabs in the US was not claimed as the media continued to promote their right wing polices (Salaita, 2012). The coverage of the Arab Spring unrest in Tunisia, Algeria, Yemen, Egypt, Libya, and Syria by five transitional Arab news channels Al Jazeera, Al Jazeera English, Al Arabiya, Alhurra and BBC Arabic revealed similarities in the media practice of applying human interest and political frames (Bruce, 2014). The media also framed the Arab Spring by using military vocabulary due to involvement of the Egyptian military in the conflict-representing civil demonstrations as a military battle.…”
Section: Literature Reviewmentioning
confidence: 99%